Análisis de los beneficios a los productores de palma africana del cantón Ventanas, provincia de Los Ríos, con la aplicación del acuerdo comercial multipartes entre Ecuador y la Unión Europea - Riofrío Angulo, Marcos Xavier (2019)
With the signing and entry into force of the Multiparty Agreement between Ecuador and the European Union, there are great economic benefits for our country, especially as regards exports of agricultural origin with 0% tariffs. Among the sectors benefited are the producers of African Palm. The present investigation was carried out in Ventanas canton, in the province of Los Ríos, since it is a sector where this activity has shown an extremely important recovery during the last years, however this does not mean that they are free of problems of all kinds. The purpose of my project is to know the current situation of the producers of African Palm of Ventanas canton, in order to provide solutions for the existing problems. Surveys were conducted aimed at small, medium and large producers and in this way to obtain fundamental information to understand the problems experienced by producers, know their shortcomings, and be able to provide solutions…..